GENDER ORIENTATION OF PUBLIC GOVERNMENT IN UKRAINE IN POST-WAR RECONSTRUCTION - ГОНЮКОВА, Лілія; КАНАВЕЦЬ, Марина; СИЧОВА, Вікторія (Київський національний університет імені Тараса Шевченка, 2023)
B a c k g r o u n d . The modern philosophy of social life, where equal rights and opportunities are guaranteed to all, is a trend of world development. Gender approaches are implemented in all areas of society. This is evidenced, in particular, by the Sustainable Development Goals (Goal 5), UN Security Council Resolution 1325 "Women. Peace. Security", the Gender Equality Strategy of the Council of Europe for 2018–2023, the European Charter for the Equality of Women and Men in the Life of Local Communities, the Biarritz Partnership etc. The implementation of gender approaches in various spheres of social life allows us to see existing problems for various social groups and individuals, to offer alternative ways of solving them, which allow us to meet the needs of specific women and specific men. The very understanding of "governance" is based on new views on the work of civil power, which reflect its turning towards citizens, democratization, and are especially important in the conditions of decentralization. The modern understanding of this term, as I. Degtyareva notes, was formed and began to be actively used in the 90s years of the 20th century to denote a modern way of managing a democratic state, when all interested parties are involved in decision-making, which significantly expands the boundaries of traditional management of government bodies. Therefore, we can talk about the transition to gender-oriented governance in modern democratic countries. The purpose of this article is to analyze the gender orientation of modern public administration of Ukraine in the conditions of post-war reconstruction. Object of study. Democratic governance in the post-war reconstruction of Ukraine. M e t h o d s . To obtain scientific results, the method of comparative analysis was used to identify similarities/differences in Ukraine's development trends, readiness for joining the EU. A comparison of the study of the projects "Strengthening the role of women in politics and decision-making at the local level" of UNDP and "Gender aspects, development of agriculture and rural areas – Ukraine" of FAO gave grounds to conclude that the processes in the regions of Ukraine are similar to the global trend: the less authority and resources are in power, the more chances women have to come to power. The method of content analysis was also used as a quantitative-qualitative method of studying the speeches of the Head of the National Agency of Ukraine on Civil Service Issues, the Vice-Prime Minister of Ukraine on European and Euro-Atlantic Integration of Ukraine, and people's deputies. R e s u l t s . In Ukraine, government officials, together with citizens, developed, wrote and implemented the State program for ensuring equal rights and opportunities for women and men, the Government approved the National Action Plan for the Implementation of the Convention on the Elimination of All Forms of Discrimination Against Women, the National Action Plan for the Implementation of UN Security Council Resolution 1325 "Women, peace, security". Departmental plans were developed and adopted for the implementation of this Plan. Amendments to normative legal acts that had discriminatory norms against women are planned and proposed for implementation. We can state that there is a real and rapid process of integration of gender approaches in all spheres of social life. The Government is also developing sectoral documents that will contribute to the development of gender-oriented public governance in the post-war period as well. At the same time, the problem remains the lack of experts on gender issues in public administration, as well as gender stereotypes that prevent effective change in society. C o n c l u s i o n s . Ukraine needs a systematic approach and consolidated actions of public authorities, civil society institutions, and business for a deeper understanding of gender approaches to the development of all spheres of our life. Post-war reconstruction will be a challenge for the implementation of a gender approach in all spheres of public life. At the same time, ensuring justice is the basic approach of public governance in European countries.

В с т у п . Актуальність і мета дослідження. Сучасна філософія суспільного життя, де рівні права і можливості гарантовані всім, є трендом світового розвитку. Гендерні підходи імплементуються в усі сфери життя суспільства. Про це свідчать, зокрема, Цілі сталого розвитку (Ціль 5), Резолюція РБ ООН 1325 "Жінки. Мир. Безпека", Стратегія гендерної рівності Ради Європи на 2018–2023 рр., Європейська хартія рівності жінок та чоловіків у житті місцевих громад, Партнерство Біарріц тощо. Імплементація гендерних підходів у різні сфери суспільного життя дає змогу побачити наявні проблеми для різних соціальних груп і окремих осіб, запропонувати альтернативні шляхи їх розв'язання, що дасть можливість задовольнити потреби конкретних жінок і конкретних чоловіків. Саме розуміння "урядування" базується на нових поглядах на роботу публічної влади, що відображають її повернення обличчям до громадян, демократизацію і особливо важливі в умовах децентралізації. Сучасне розуміння цього терміна, як зазначає І. Дегтярьова, сформувалось і почало активно використовуватись у 90-х роках ХХ ст. для позначення сучасного способу управління демократичною державою, коли до ухвалення рішень залучаються всі зацікавлені сторони, що значно розширює межі традиційного управління органів влади. Тому ми можемо говорити про перехід до гендерно орієнтованого врядування у сучасних демократичних країнах. Метою статті є аналіз гендерної орієнтованості сучасного публічного управління України в умовах післявоєнної відбудови. Об'єкт дослідження – демократичне врядування у післявоєнній відбудові України. М е т о д и . Для отримання наукових результатів було використано метод порівняльного аналізу з метою виявлення схожості / розбіжності тенденцій розвитку України, готовності вступу до ЄС. Порівняння дослідження проєктів "Посилення ролі жінок у політиці та прийнятті рішень на місцевому рівні" ПРООН і ФАО "Гендерні аспекти, розвиток сільського господарства та сільських територій – Україна" дало підстави зробити висновок про подібність процесів у регіонах України до світової тенденції: чим менше повноважень і ресурсів є у влади, тим більше шансів мають жінки прийти у владу. Також було застосовано метод контент-аналізу як кількісно-якісний метод вивчення промов голови Національного агентства України з питань державної служби, віцепрем'єр-міністра України з питань європейської та євроатлантичної інтеграції України, народних депутатів. Р е з у л ь т а т и . В Україні урядовцями спільно з громадянами напрацьована, написана і діє Державна програма забезпечення рівних прав та можливостей жінок і чоловіків. Урядом затверджено Національний план дій із виконання Конвенції про ліквідацію усіх форм дискримінації щодо жінок, Національний план дій з виконання резолюції Ради Безпеки ООН 1325 "Жінки, мир, безпека". На виконання цього Плану було розроблено та прийнято відомчі плани. Заплановано та пропонуються до впровадження зміни до нормативно-правових актів, що мали дискримінаційні норми стосовно жінок. Ми можемо констатувати, що відбувається реальний та швидкий процес інтеграції гендерних підходів у всі сфери суспільного життя. В уряді також розробляються секторальні документи, що сприятимуть розвитку гендерно орієнтованого публічного врядування і в повоєнний час. Водночас проблемою залишається брак фахівців із гендерної проблематики в публічному врядуванні, а також гендерні стереотипи, що заважають ефективно змінювати суспільство. В и с н о в к и . Україні потрібен системний підхід та консолідовані дії органів публічної влади, інститутів громадянського суспільства, бізнесу для поглибленого розуміння гендерних підходів до розвитку всіх сфер нашого життя. Післявоєнна відбудова буде викликом для реалізації гендерного підходу в усіх сферах суспільного життя. Водночас саме забезпечення справедливості є базовим підходом публічного врядування європейських країн.
ГЕНДЕРНА ОРІЄНТАЦІЯ ПУБЛІЧНОГО ВРЯДУВАННЯ В УКРАЇНІ В ПІСЛЯВОЄННІЙ ВІДБУДОВІ
Keywords: гендер; гендерно орієнтоване врядування; гендерно-правова експертиза; гендерний аудит; гендерно орієнтований бюджетний процес; післявоєнна відбудова.